2021
DOI: 10.1111/cen.14623
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pharmacological interventions on insulin resistance in women with polycystic ovary syndrome: A systematic review and meta‐analysis of randomized controlled trials

Abstract: Objective Polycystic ovary syndrome (PCOS) is a complex endocrine condition affecting women of reproductive age. It is characterized by insulin resistance and is a major risk factor for type 2 diabetes mellitus (T2DM). The objective was to review the literature on the effect of different pharmacological interventions on insulin resistance in women with PCOS. Design We searched PubMed, MEDLINE, Scopus, Embase, Cochrane library and the Web of Science in April 2020 and updated in March 2021. The study follows the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 91 publications
0
4
0
Order By: Relevance
“…Pioglitazone relieves insulin resistance by activating PPAR-γ to affect gene transcription related to glucose and lipid metabolism. 5 , 6 In addition, the Chinese guidelines for the diagnosis and treatment of PCOS in 2018 proposed that acarbose, as an alpha glycosidase inhibitor, not only reduces and slows the intestinal absorption of glucose but also increases insulin sensitivity, rectifies lipid metabolic disorders, and advances gastrointestinal function. Previous studies have also shown that acarbose adjusts the menstrual cycle of obese PCOS patients and that it can be used for the treatment of metabolic disorders in PCOS patients.…”
Section: Introductionmentioning
confidence: 99%
“…Pioglitazone relieves insulin resistance by activating PPAR-γ to affect gene transcription related to glucose and lipid metabolism. 5 , 6 In addition, the Chinese guidelines for the diagnosis and treatment of PCOS in 2018 proposed that acarbose, as an alpha glycosidase inhibitor, not only reduces and slows the intestinal absorption of glucose but also increases insulin sensitivity, rectifies lipid metabolic disorders, and advances gastrointestinal function. Previous studies have also shown that acarbose adjusts the menstrual cycle of obese PCOS patients and that it can be used for the treatment of metabolic disorders in PCOS patients.…”
Section: Introductionmentioning
confidence: 99%
“…66 Most of their important effects were also illustrated in several recent meta-analyses; monotherapy with GLP-1R agonists or their combination with MET were superior to MET monotherapy in terms of reduction of waist circumference, body weight and BMI. [67][68][69][70][71][72][73] In order to enhance the cardiometabolic and hormonal defects associated with this syndrome, the potential combination of GLP-1R agonists/sodium-glucose co-transporter 2 (SGLT2) inhibitors is also being studied. 57,74 Decreased free T levels and FAI have been shown both after LIRA and EXE administration.…”
Section: Discussionmentioning
confidence: 99%
“…A preplanned protocol was registered in the International Prospective Register of Systematic Reviews (PROSPERO, CRD42016050444) by the recommendations of the Cochrane Handbook for Systematic Reviews of Interventions [18]. Furthermore, our review is described based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines [19].…”
Section: Methodsmentioning
confidence: 99%